2019
DOI: 10.1039/c8ra10195g
|View full text |Cite
|
Sign up to set email alerts
|

Seven new cytotoxic phenylspirodrimane derivatives from the endophytic fungus Stachybotrys chartarum

Abstract: The diverse structures and anticancer activities of phenylspirodrimane derivatives are investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…It was found that 51 and 105 – 108 had cytotoxic potential versus U-2OS and MDA-MB-231 (IC 50 s 4.5–21.7 µM). Besides, 51 and 107 demonstrated powerful anti-proliferation and anti-apoptosis effectiveness versus U-2OS cells, while all metabolites had no influence (IC 50 >50 µM) versus MCF-7 cells [ 70 ]. These data may provide evidence for further research into the anticancer activities of these compounds.…”
Section: Secondary Metabolites From S Chartarummentioning
confidence: 99%
“…It was found that 51 and 105 – 108 had cytotoxic potential versus U-2OS and MDA-MB-231 (IC 50 s 4.5–21.7 µM). Besides, 51 and 107 demonstrated powerful anti-proliferation and anti-apoptosis effectiveness versus U-2OS cells, while all metabolites had no influence (IC 50 >50 µM) versus MCF-7 cells [ 70 ]. These data may provide evidence for further research into the anticancer activities of these compounds.…”
Section: Secondary Metabolites From S Chartarummentioning
confidence: 99%
“…In addition, Stachybotrys has been detected on damp paper, cotton, linen, cellulose-based building materials (drywalls, wallpapers in indoor environments), water-damaged indoor buildings, and air ducts [ 5 , 17 , 19 , 28 , 31 , 32 , 33 , 34 , 35 ]. Most Stachybotrys species are cellulolytic saprobes [ 36 ], as well as plant pathogens [ 37 , 38 ] and endophytes [ 39 , 40 , 41 , 42 , 43 ]. Memnoniella species exhibit saprobic lifestyles and have been reported from dead plant materials and soil [ 20 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most Stachybotrys species are cellulolytic saprobes [ 36 ], as well as plant pathogens [ 37 , 38 ] and endophytes [ 39 , 40 , 41 , 42 , 43 ]. Memnoniella species exhibit saprobic lifestyles and have been reported from dead plant materials and soil [ 20 , 39 ]. Some taxa of Memnoniella and Stachybotrys ( M. echinata and S. chartarum ) coexist in similar ecological habitats such as indoor environments [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations